Parting the Clouds: Three Professionalism Frameworks in Medical Education. (December 2016) - Irby, David M.; Hamstra, Stanley J.
Abstract : Current controversies in medical education associated with professionalism, including disagreements about curriculum, pedagogy, and assessment, are rooted in part in the differing frameworks that are used to address professionalism. Three dominant frameworks, which have evolved in the medical education community, are described. The oldest framework is virtue based and focuses on the inner habits of the heart, the development of moral character and reasoning, plus humanistic qualities of caring and compassion: The good physician is a person of character. The second framework is behavior based, which emphasizes milestones, competencies, and measurement of observable behaviors: The good physician is a person who consistently demonstrates competence in performing patient care tasks. The third framework is identity formation, with a focus on identity development and socialization into a community of practice: The good physician integrates into his or her identity a set of values and dispositions consonant with the physician community and aspires to a professional identity reflected in the very best physicians. Although each professionalism framework is useful and valid, the field of medical education is currently engaged in several different discourses resulting in misunderstanding and differing recommendations for strategies to facilitate professionalism. In this article, the assumptions and contributions of each framework are described to provide greater insight into the nature of professionalism. By examining each discourse in detail, underlying commonalities and differences can be highlighted to assist educators in more effectively creating professionalism curricula, pedagogy, and assessment.